Electrocardiographic characteristics of patients with coronavirus disease 2019 (COVID-2019) related pneumonia at first presentation. (24th May 2021) - Nguyen, U; Strik, M; Abu-Arib, S; Bruekers, A; Nguyen, T; Massud, A; Willems, R; Dekker, S; Spaetgens, B; Engels, E; Crijns, HGJM; Koopmans, R; et al.
Abstract: Funding Acknowledgements: Type of funding sources: None. Purpose: To evaluate electrocardiographic (ECG) characteristics at first presentation in patients with possible coronavirus disease (COVID-19) pneumonia. Methods and results: 356 patients presenting at the emergency room with possible COVID-19 pneumonia based on clinical presentation and computed tomography findings were included and subdivided into a COVID-19 positive group ([COVID-19-positive], n = 231, 65%) and a COVID-19 negative group ([COVID-19-negative], n = 125, 35%) based on polymerase chain reaction tests. The study population was predominantly middle aged-elderly (67 ± 14 year; n = 235, 66% male). Mortality rate was 24% after 1-month follow-up. There were no significant (NS) differences in sex, age, and mortality between the COVID-19-positive and COVID-19-negative group. Atrial fibrillation (AF) was common (9%), though its prevalence was NS (regression analyses adjusted for age and sex) different in the COVID-19-positive vs. the COVID-19-negative group. ECG characteristics reflecting atrial enlargement and repolarization abnormalities were frequently present (<38% and 14% respectively). No significant differences were found between the COVID-19-positive vs. the COVID-19-negative group for the majority of morphological ECG characteristics (Figure 1 for more detailed data). Conclusion: AF and ECG characteristics reflecting atrial enlargement and repolarization abnormalities are commonly present in COVID-19 patients. The prevalence of these ECG characteristics however do NS differ from their COVID-19-negative counterparts.